Morphable 3D-Mosaics: A Hybrid Framework for Photorealistic Walkthroughs of Large Natural Environments. (18th May 2008) - Komodakis, Nikos; Tziritas, Georgios
Abstract : This paper presents a hybrid (geometry- & image-based) framework suitable for providing photorealistic walkthroughs of large, complex outdoor scenes at interactive frame rates. To this end, based just on a sparse set of real stereoscopic views from the scene, a set of morphable 3D-mosaics is automatically constructed first, and then, during rendering, a continuous morphing between those 3D-mosaics that are nearby to the current viewpoint is taking place. The morphing is both photometric, as well as geometric, while we also ensure that it proceeds in a physically valid manner, thus remaining transparent to the user. The effectiveness of our framework has been demonstrated in the 3D visual reconstruction of the Samaria Gorge in Crete, which is one of the largest and most beautiful gorges in Europe.